Alden Weissfeld: capstone - Weissfeld, Alden, artist (Colorado State University. Libraries, 2016)
The artist's statement: My art is an exploration of color and form as it relates to the unseen beauty found in the small corners of the world. I start my exploration through photography of a microcosmic world. The pictures I take are manipulated to the degree that the original subject matter has become completely abstracted. The changes I make to the images are concerned with finding and enhancing the unexpected textures and colors. Transforming the mundane and ordinary such as: burnt milk on the bottom of a pot or rust cascading down the roof of a small outdoor fire metal pit into images full of life and energy. To me, this imagery serves as an interesting challenge, I find that the search for the right textures (i.e. the difference between marks) mixed with the right color (i.e. the vibrancy, hue, and overall effect of a color) satisfies my inner need to create and explore. In the end, all I can say is that my art is genuine in its intent.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting